Vaginal microbiota of adolescents and their mothers: A preliminary study of vertical transmission and persistence - Bassis, Christine M.; Bullock, Kaylie A.; Sack, Daniel E.; Saund, Katie; Pirani, Ali; Snitkin, Evan S.; Alaniz, Veronica I.; Quint, Elisabeth H.; Bell, Jason D.; Young, Vincent B. (Frontiers in Microbiomes, 2023)
Factors that influence vaginal microbiota composition, including its source, are not well understood. To determine if vaginal microbiota transmission from mother to daughter at birth could possibly influence the human vaginal microbiota composition in adolescence, we conducted a preliminary study to investigate the relationship between the vaginal microbiota of 13 adolescents (ages 15-21) and their mothers and the daughter’s birth mode. Based on analysis of bacterial 16S rRNA gene sequences, the vaginal microbiotas of mother/daughter pairs were more similar to each other if the daughter was born by vaginal delivery rather than by C-section. Specifically, within pair beta-diversity, measured by the Yue and Clayton θ (θYC) distance metric, was significantly lower if the daughter was born by vaginal delivery. Additionally, genome sequences from an important member of the vaginal microbiota, Lactobacillus crispatus, isolated from one mother/daughter pair in which the daughter was born by vaginal delivery, were highly similar based on recombination-filtered single nucleotide polymorphisms (SNPs). Both community-level analysis and isolate genome sequence analysis are consistent with birth-mode dependent transmission and persistence of at least some members of the vaginal microbiota.